The implementation of Work Improvement in Small Enterprises (WISE) to Enhance The Quality and Hygiene of The Work Environment - Pamungkas, Dicky; Iftadi, Irwan (Faculty of Industrial Technology Universitas Islam Indonesia, 2025)
A healthy and safe working environment is essential for enhancing productivity and ensuring worker well-being, especially in small enterprises such as UMKM (Micro, Small, and Medium Enterprises). Despite their importance, many UMKMs struggle to meet hygiene and safety standards due to limited resources and lack of awareness. This study evaluates the workplace conditions at a tofu-processing UMKM and identifies key barriers to improving environmental quality and hygiene. The research utilised the Work Improvement in Small Enterprises (WISE) approach, which involves step-by-step activities including workplace observation, hazard identification, issue prioritization, implementation of improvements, and follow-up evaluation. The most critical problems identified were the absence of SOPs, lack of safety signs, and inadequate sanitation facilities. Solutions were developed using the WISE method, including SOP drafting, safety signage installation, and sanitation enhancement. The implementation of WISE has proven effective in improving workplace hygiene and safety, offering a practical model for similar small enterprises.